Managerial turnover and performance in outside boards: Ownership makes the difference - Lafuente, Esteban (2019)
We examine the relationship between CEO, board and Chairman turnovers and future performance in banks with fully outside boards. Using a rich dataset on executive turnovers from Costa Rica, we find that ownership moderates the effect that control mechanisms have on performance. Our results indicate that executive turnovers followed by the appointment of outside executives (CEO and Chairman) have a positive impact on performance. On the contrary, large board replacements create organisational costs and these negatively affect performance. These results mainly hold for shareholder-oriented banks where managers and owners are more likely to be aligned. Finally, these results underline the importance of examining the effectiveness of governance mechanisms in emerging economies. More detailed information about ownership, legal framework and executive replacements can make a difference when it comes to evaluate the effectiveness of governance mechanisms.